Codesign: a interação projetual entre organizações e atores externos no processo de desenvolvimento de novos produtos - Hanauer, Rodrigo (Universidade do Vale do Rio dos Sinos, 2013)
The process of new product development is presented as a more collaborative practice. From an open innovation model that recognizes the value of ideas generated outside its limits, companies come to insert external participants in various stages of the value creation chain. From this, our goal is to analyze the interaction between external actors and organizations that occurs specifically in the design stage of new product development, in a process called co-design. For this, is developed an action research that involves a co-design project between company, users of their products and other external participants, focusing into the involvement of the designer and its role in mediating project interactions. The main results are the discussion of the collective generation of knowledge in a co-design process performed in the organizational context, the identification of the actors and their roles, the role of online platforms, the use of projective tools. Finally, the research points to the possibility of co-design assuming a strategic value for organizational development.
Keywords: Design; Codesign; Interação; Organização; Usuários; Atores externos; Co-design; Interaction; Organization; Users; External actors; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial